(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Enteric fever is an important public health problem in developing countries including Bangladesh. A changing antibiotic sensitivity pattern of Salmonella typhi and emergence of resistance has increased to a great concern. Objective: Aim of the study was to investigate the antibiotic sensitivity pattern of Salmonella typhi. Methods: A total of 181 Salmonella typhi samples from 5 to 15 years age group were collected from blood culture during the period of October to December 2014 from IBN SINA Hospital, Dhaka, Bangladesh. Specimens from the blood culture were identified by standard procedures as needed. Antimicrobial susceptibility testing was performed by disk diffusion method according to The Clinical Laboratory Standard Institute guidelines. Results: Among the tested antibiotics, S. typhi was susceptible to ceftriaxone 100%, followed by cefixime and gentamicin 99.4%, ciprofloxacin 98.6%, cotrimoxazole 88.9%, azithromycin 88.4 % and least susceptible antibiotic was Ampicillin 62.5% and nalidixic acid 5%. Conclusion: The antimicrobial sensitivity testing showed that the Salmonella typhi were highly sensitive (>88%) to most of the drugs used in this study, whereas nalidixic acid showed only 5% sensitivity. So this study indicates that ceftriaxone, cefixime, gentamicin and ciprofloxacin can be used as a first line therapy and nalidixic acid should be avoided for treatment. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.416-418